Smart briefing: plataforma de captaçãço de briefing automatizada - Queiroz, Paola Danyelle Novaes (2020)
This project has an objective to develop a prototype of a plataform that solves the challenges faces day by day at the publicity agencies, such as the difficulty in collecting information about visual preferences. The interviews that normally leads to the conception of briefing, usually doesn’t generate exact data about how to proceed to create the publicity material. It is noticed that the clients of this type of service provider in the majority are small businessmen who do not have a great structure of communication and marketing, but they need the services of an agency and, besides the lack of a strategic planning structure for their communication they do not have the financial resources to hire a consultant to do this survey. In addition, the profile of the clients that hire ad agencies services is of a demanding and rigorous customer regarding quality and deadlines. Given this scenario, it is necessary to create ways to improve this information collection and strategic planning of the campaigns, but without costing agencies. In search of offering a tool that collaborates with this survey of customer data and preferences it is intended to develop a platform that can trace the creative direction from an interactive questionnaire and based on behavioral bases that selects customer preferences visually and beside this, the feedback (provided by agencies clients) can improve the experience of the client and the communication service provider